Anorectal physiology and transit in patients with disorders of thyroid metabolism - Deen, K.I.; Seneviratne, S.L.; de Silva, H.J. (Blackwell Scientific Publications, 1999)
BACKGROUND: Data on anorectal physiology in patients with disordered thyroid metabolism are lacking. This prospective study was performed to evaluate anorectal physiology in patients with either hyperthyroidism and diarrhoea, or hypothyroidism and constipation in order to assess slow transit in hypothyroid patients. METHODS: Thirty patients with hypothyroidism and constipation (24 females, median age 59 years, range 23-80) and 20 patients with hyperthyroidism and diarrhoea (12 females, median age 46 years, range 36-62) were evaluated by anal manometry, rectal balloon sensation and whole-gut transit markers. Data were compared with anorectal physiology and whole-gut transit in 22 healthy controls (13 females, median age 51 years, range 24-65). RESULTS: In the hypothyroid patients, maximum resting pressure (MRP) and maximum squeeze pressure (MSP) were similar to controls (patients, median MRP 55 mmHg (18-98); controls, median MRP 41 mmHg (20-105) and patients, median MSP 83 mmHg (39-400); controls, median MSP 88 mmHg (30-230); P 0.05 for both resting and squeeze pressures). In hyperthyroid patients, median MRP and MSP were significantly lower than controls (patients, MRP 33 mmHg (8-69); controls MRP 41 mmHg (20-105) P = 0.04 and patients, MSP 60 mmHg (26-104); controls, MSP 88 mmHg (30-230); P = 0.03). Threshold sensation for impending evacuation in hypothyroid patients was significantly higher than controls, while in hyperthyroid patients, threshold sensation was significantly lower compared with controls. Maximum tolerable rectal volumes in hypothyroid patients was significantly lower compared with controls, while no significant difference was found between maximum tolerable rectal volumes in hyperthyroid patients and controls. Prevalence of delayed whole-gut transit in both hypothyroid and hyperthyroid patients was similar to controls. Furthermore, 33 percent of hypothyroid patients and 40 percent of hyperthyroid patients experienced symptoms of bowel dysfunction prior to the onset of their thyroid disorder. CONCLUSIONS: Patients with altered thyroid function and bowel dysfunction demonstrated abnormalities of anal manometry and rectal sensation.
Indexed in MEDLINE
Keywords: Anal Canal-physiopathology; Case-Control Studies; Constipation-physiopathology; Diarrhea-physiopathology; Hyperthyroidism-physiopathology; Hypothyroidism-physiopathology; Prospective Studies